Factors Contributing to TB at Primary Health Center in Sidoarjo - Indonesia - Totok Indarto; Tintin Sukartini; Makhfudli Makhfudli (Universitas Airlangga, 2020)
Introduction: Tuberculosis (TB) is caused by Mycobacterium tuberculosis, and remains a burden in Indonesia. Many factors contribute to the TB prevalence, including age, sex, body mass index, sputum smear conversion, HIV infection, and Diabetes Mellitus. The objective of this study is to identify factors contributing to TB prevalency at the primary health center.Methods: This research used as a cross-sectional study and was conducted in March 2020. The population of this study was TB patients at Porong Primary Health Center in Sidoarjo, East Java Province, Indonesia. Samples were all TB patients who registered in Porong Primary Health Center and were taken by total sampling. The sample size was 51 TB patients. There were no inclusion and exclusion samples criteria implemented. Data were collected that used the secondary data of TB Patients Registration, between 1st – 31st March April 2020. Data were analyzed using frequency distribution with SPSS Version 21.Results: Result shows there were 30 (58.80%) male TB patients, 34(66.70%) TB patients were adults, 48 (94.10%) TB patients had sputum smear conversion from positive to negative after two months DOTS therapy, there were 48 (94,10%) TB patients not infected by HIV Virus, and there were 36 (70,60%) TB patients had a history of Diabetes Mellitus.Conclusion: Factors contributing to TB prevalence are many, including age, sex, body mass index, sputum smear conversion, HIV infected, and Diabetes Mellitus. To improve care of TB patients requires integration and comprehension of care at the primary health center.